1998
DOI: 10.5962/bhl.title.4128
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative composition and distribution of the macrobenthic invertebrate fauna of the continental shelf ecosystems of the northeastern United States / Roger B. Theroux, Roland L. Wigley.

Abstract: From the mid-1950s to the mid-1 960's a series of quantitative surveys of the macrobenthic invertebrate fauna were conducted in the offshore New England region (Maine to Long Island, NewYork). The surveys were designed to 1) obtain measures of macrobenthic standing crop expressed in terms of density and biomass; 2) determine the taxonomic composition of the fauna (ca. 567 species): 3) map the general features of macrobenthic distribution; and 4) evaluate the fauna's relationships to water depth, bottom tvpe, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 9 publications
1
50
1
Order By: Relevance
“…Steimle (1987) used literature values of P:B ratios to estimate benthic production on the Bank. Total production based on the Theroux and Wigley (1998) samples is 102 kcal m -2 .yr -1 with an overall P:B ratio of 1.2 (Table 10 ). The same P:B ratios, applied to Michael et al's (1983) (Table 10).…”
Section: Benthic Faunamentioning
confidence: 99%
See 1 more Smart Citation
“…Steimle (1987) used literature values of P:B ratios to estimate benthic production on the Bank. Total production based on the Theroux and Wigley (1998) samples is 102 kcal m -2 .yr -1 with an overall P:B ratio of 1.2 (Table 10 ). The same P:B ratios, applied to Michael et al's (1983) (Table 10).…”
Section: Benthic Faunamentioning
confidence: 99%
“…Diet information has been compiled for 24 benthic species that are abundant on Georges Bank (Theroux & Wigley, 1998). The suspension feeders filter microplankton (diatoms, flagellates and microzooplankton) and the deposit feeders consume organic matter on sediment grains.…”
Section: Benthic Faunamentioning
confidence: 99%
“…The few studies that have attempted to synoptically sample the benthos at these broad scales literally took multiple decades to sample, process, identify, audit and analyze (e.g. Kiyko & Pogrebov 1997, Theroux & Wigley 1998. Thus, it is difficult, time-consuming, and cost-prohibitive to survey benthos, let alone determine the broad-scale and long-term dynamics of benthic communities or the extent of effects on benthic communities from fishing and similar disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of daytime beam trawl sampling may have influenced our results because some species have been found to exhibit diel patterns of microhabitat use on the northeast U.S. shelf (Diaz et al, 2003); consequently additional roundthe-clock sampling may lead to the discovery of different habitat relationships than those we report here. Nevertheless, taxon-specific relationships with habitat on the shelf have previously been shown for fish and macro-invertebrates and were most closely associated with sediment characteristics (Wigely and Theroux, 1981;Theroux and Wigely, 1998;Methratta andLink, 2006, 2007), depth (in both the cross-shelf and shoal formations) (Viscido et al, 1997;Steves et al, 1999;Methratta and Link, 2007;Vasslides and Able, 2008;Slacum et al, 2010), and bottom water temperature, particularly with seasonal temperature changes (Steves et al, 1999;Malek et al, 2014). Hale (2010), in examining estuarine and near shore sample locations, also showed that salinity was related to macro-invertebrate assemblages.…”
Section: Cca1 (182%)mentioning
confidence: 85%
“…3). Regional variation in assemblage structure on the northeast U.S. shelf, following a south to north gradient, has been described for both fish (Gabriel, 1992;Lucey and Nye, 2010) and macro-invertebrates (Wigely and Theroux, 1981;Theroux and Wigely, 1998;Hale, 2010). Consequently, impacts of WEAs spread along the shelf may become additive for assemblages that span large distances (i.e., 50-100 km).…”
Section: Cca1 (182%)mentioning
confidence: 99%